Aktivitas Antioksidan Ekstrak Etanol dan Fraksi Etil Asetat Daun Senduduk (Melastoma Malabathricum L) Metode DPPH (2,2-Diphenyl-1-Picrylhydrazyl) - Sri Hainil; Delladari Mayefis; Rika Wahyuni (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Senduduk leaf is a plant that is a plant that contains secondary metabolites, including alkaloids, flavonoids, saponins, terpenoids, and tannins. Antioxidants are compounds that can delay, slow down and prevent free radicals. This research was conducted to determine and compare the antioxidant activity of ethanol extract and ethyl acetate fraction of senduduk leaves. The method used in this study is the DPPH (2,2-Diphenyl-1-Pickrylhydrazyl) method. From the phytochemical screening test, senduduk leaves were positive for alkaloids, flavonoids, saponins, terpenoids and tannins. Determination of antioxidant activity was carried out by the DPPH method at a wavelength of 517 nm. The percentage of inhibition of ethanol extract of senduduk leaves was obtained by 80% and percent of inhibition of ethyl acetate fraction was obtained by 92% while the percentage of inhibition of Vitamin C was obtained by 96%, it can be concluded that ethanol extract and ethyl acetate fraction of senduduk leaves have antioxidant activity in a fairly high category. and almost close to the percent inhibition of Vitamin C. Ethyl acetate fraction of senduduk leaves has a higher antioxidant activity value than ethanol extract.